The Factors Affecting Human Understanding of the Perceived World in the Novel “Room” by Emma Donoghue: An Analysis of the Lead Character - Nirwana, Nirwana; Khaswar, Nurul (Elsya : Journal of English Language Studies, 2020)
This study is intended to describe the factors affecting human understanding of the perceived world based on John Locke’s theory by analysing the lead character of Emma Donoghue’s novel Room . Locke divided the way people gaining human understanding of knowledge through experience in two ways which are from sensory experience and inner experience. By using qualitative approach this study extracted Jack’s experience and categorise in to sensory experience and inner experience which is related to his understanding of the perceived world. Between the sensory and the inner experience, they connected with each other, the experience gained from the eyes will be remembered by the inner experience, and what is smelled by the nose will be remembered by the inner experience. From sensory and inner experience, they produce knowledge and knowledge influence their perception. Every person has a different experience from their respective sensory and their experience affecting perception.